2012
DOI: 10.1371/journal.pone.0040601
|View full text |Cite
|
Sign up to set email alerts
|

Fast Recruitment of Recurrent Inhibition in the Cat Visual Cortex

Abstract: Neurons of the same column in L4 of the cat visual cortex are likely to share the same sensory input from the same region of the visual field. Using visually-guided patch clamp recordings we investigated the biophysical properties of the synapses of neighboring layer 4 neurons. We recorded synaptic connections between all types of excitatory and inhibitory neurons in L4. The E–E, E–I, and I–E connections had moderate CVs and failure rates. However, E–I connections had larger amplitudes, faster rise-times, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 75 publications
4
24
0
Order By: Relevance
“…This assumption is approximately supported by the experimental evidence (Ohana et al, 2012), but we cannot assume it holds exactly in a real biological substrate. However, we hypothesize, that the small discrepancies between the delay of the mono-synaptic excitatory connections and the cumulative delay of the bi-synaptic inhibitory interactions can be absorbed into the membrane time-constant of the neurons.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…This assumption is approximately supported by the experimental evidence (Ohana et al, 2012), but we cannot assume it holds exactly in a real biological substrate. However, we hypothesize, that the small discrepancies between the delay of the mono-synaptic excitatory connections and the cumulative delay of the bi-synaptic inhibitory interactions can be absorbed into the membrane time-constant of the neurons.…”
Section: Resultsmentioning
confidence: 64%
“…A recent study by Ohana et al (2012) revealed a specific pattern of transmission delays between different neural type combinations. Specifically they found that the excitatory to excitatory connections are slow, while the excitatory to inhibitory connections are fast.…”
Section: Introductionmentioning
confidence: 95%
“…To reflect this, for all intra-cortical connectivity a distance-dependent delay with propagation constant of 0.3 ms −1 (Bringuier et al 1999;Frégnac 2012;Chavane et al 2011) was used, which corresponds to the slow propagation of action potentials along the intra-V1 (lateral) un-myelinated axons. The delays in the feed-forward thalamo-cortical pathway are drawn from a uniform distribution within the range (1.4,2.4) ms. Second, Ohana et al (2012) have recently shown that delays of synaptic transmission in cat visual cortex are dependent on both pre-and post-synaptic neural type, with the notable feature of slow excitatory to excitatory and fast excitatory to inhibitory transmission. Distance-dependent axonal propagation delay is unlikely to explain these results as these experiments were performed in nearby neurons (Ohana et al 2012).…”
Section: Delaysmentioning
confidence: 99%
“…The delays in the feed-forward thalamo-cortical pathway are drawn from a uniform distribution within the range (1.4,2.4) ms. Second, Ohana et al (2012) have recently shown that delays of synaptic transmission in cat visual cortex are dependent on both pre-and post-synaptic neural type, with the notable feature of slow excitatory to excitatory and fast excitatory to inhibitory transmission. Distance-dependent axonal propagation delay is unlikely to explain these results as these experiments were performed in nearby neurons (Ohana et al 2012). These pair-specific synaptic integration delays are in the order of only a few ms, but are important for local integration (within the same column) and for the precise timing of spike control by E/I interaction.…”
Section: Delaysmentioning
confidence: 99%
“…The delays in the feed-forward thalamo-cortical pathway are drawn from a uniform distribution within the (1.4,2.4) ms −1 range. Second, Ohana et al [56] have recently shown that delays of synaptic transmission in cat visual cortex are dependent on both pre-and post-synaptic neural type, with the notable feature of slow excitatory to excitatory and fast excitatory to inhibitory transmission. Distance-dependent axonal propagation delay is unlikely to explain these results as these experiments were performed in nearby neurons [56].…”
Section: Delaysmentioning
confidence: 99%